Identifikasi Aspek-Aspek Ketidakamanan Kerja (Job Insecurity) pada Guru Honorer di Sekolah Pinggiran - Doddy Hendro Wibowo; Dwi Setya Ariani (Jurnal Ilmiah Psikologi MIND SET, 2016)
The honorary teachers are teachers who do not have permanent status or teachers who have not been appointed as civil servants. Problems of temporary teacher not only related to their employment status but also with the school which labeled as marginal school. This situation makes the honorary teachers have insecure feeling associated with their work (job insecurity). This study involved 121 honorary teachers from 34 educational institutions from kindergarten, elementary school, Junior High School, and Senior High School in the suburban area in Salatiga. This research used Job Insecurity Scale (JIS). The research found the job insecurity of honorary teacher in Salatiga which was dominized as moderate categorization. In particular, the highest source of job insecurity for honorary teacher in suburban area in Salatiga is a low possibility to be promoted in suburban school.